Functional and Immunological Characterization of a Duffy Binding–Like–γ Domain from Plasmodium falciparum Erythrocyte Membrane Protein–1 Expressed by a Placental Isolate - Chia, Yu-Shan; Badaut, Cyril; Tuikue Ndam, Nicaise G.; Khattab, Ayman; Igonet, Sebastien; Fievet, Nadine; Bentley, Graham A.; Deloron, Philippe; Klinkert, Mo-Quen (The Journal of infectious diseases, 2005)
A recombinant Duffy binding–like (DBL)–γ domain from a previously identified placental isolate, 732, was expressed by use of the baculovirus/insect cell system and was purified in milligram quantities. The recombinant protein binds specifically to chondroitin sulfate A (CSA) and inhibits CSA binding by placental infected erythrocytes (IEs). Polyclonal antibodies raised against the domain recognized the surfaces of live IEs from CSA-adherent clinical placental isolates. These antibodies also abrogated the in vitro binding of IEs to CSA. The 732 DBL-3γ domain was specifically recognized by plasma from pregnant women but not by plasma from control subjects. In addition, the protein was, comparatively, significantly more reactive with plasma from women with infected placentas, strongly suggesting that the 732 DBL-3γ domain carries preferentially IE-expressed immunogenic epitopes. High levels of plasma antibodies to the recombinant domain were associated with reduced placental parasite density. This is the first report of a recombinant DBL-γ domain derived from a placental isolate that shows CSA-binding properties